Approach to analysis of technical -organizational system functioning on the base of semi-markov process theory - Gavrilin, Aleksey; Gorbunova, Tatiana; Tumanova, Marina; Ratnikov, Oleg (International Journal of Engineering and Technology, 2018)
Relevance of the present task lays in optimization of control over complex systems considering probabilistic and temporal nature of their functioning. Allocated some generic States of the system's normal operation and consider destabilizing situations when the continued functioning of the element in the system becomes difficult, impossible. Including the status when it is necessary to conduct full diagnostic and restoring of the system with explicit damage which makes it impossible for the system to operate in the acceptable mode into the model is described in the work. The proposed solution to this task is based on the mathematical modelling. Considering the general case of nonexponential time of system residence in its own status, the proposed functioning model displays relations between system statuses and probable parameters of its functioning on the base of semi-Markov process theory. Because of this work the explanation of an adequate description of complex system functioning at probabilistic and temporal analysis was presented.Â Â